2014
DOI: 10.1111/cas.12395
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin enhances apoptotic effect of tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL) in ovarian cancer cells through reactive oxygen species (ROS) mediated CCAAT enhancer‐binding protein homologous protein (CHOP)‐death receptor 5 pathway

Abstract: Although tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has shown efficacy in a phase 2 clinical trial, development of resistance to TRAIL by tumor cells is a major roadblock. We investigated whether quercetin, a flavonoid, can sensitize human ovarian cancer cells to TRAIL. Results indicate that quercetin sensitized cancer cells to TRAIL. The quercetin induced expression of death receptor DR5 but did not affect expression of DR4 in cancer cells. The induction of DR5 was mediated through activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 30 publications
(61 reference statements)
13
75
0
Order By: Relevance
“…Various studies have reported the increased transcriptional activation of DR5 gene by the upregulation of CHOP expression (41)(42)(43)(44)(45), these correlated to the upregulation of CHOP expression in goniothalamin treatment. Another mechanism which is involved in sensitization to TRAIL-induced apoptosis is downregulation of cFLIP and Mcl1.…”
Section: Discussionmentioning
confidence: 92%
“…Various studies have reported the increased transcriptional activation of DR5 gene by the upregulation of CHOP expression (41)(42)(43)(44)(45), these correlated to the upregulation of CHOP expression in goniothalamin treatment. Another mechanism which is involved in sensitization to TRAIL-induced apoptosis is downregulation of cFLIP and Mcl1.…”
Section: Discussionmentioning
confidence: 92%
“…According to the authors, the combination of quercetin with TRAIL did not affected on DR5 receptor expression, ROS (important upstream signals required for the upregulation of death receptors; capable to induce CHOP expression) [59] mediated endoplasmic reticulum-stress (ERS) [58]. In this study a combined treatment of the cells with both TRAIL and quercetin showed significantly higher cell death compared to TRAIL or quercetin applied alone.…”
Section: Chemoprotective Activities In Ovarian Cancer Cells Of Quercementioning
confidence: 53%
“…Recently, an enhancement by quercetin (50 μM, 100 μM, 200 μM) of apoptotic death of human ovarian cancer SKOV-3, OVCAR-3 and TOV-21G cells to the presence of the tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) (25 ng/ml) through activation of JNK cellular signal transduction kinase, upregulation of a transcription factor CCAAT enhancer-binding protein (C⁄EBP)) homologous protein (CHOP), induction of cell death receptor DR5, activated by TRAIL [56,57], was observed [58]. According to the authors, the combination of quercetin with TRAIL did not affected on DR5 receptor expression, ROS (important upstream signals required for the upregulation of death receptors; capable to induce CHOP expression) [59] mediated endoplasmic reticulum-stress (ERS) [58].…”
Section: Chemoprotective Activities In Ovarian Cancer Cells Of Quercementioning
confidence: 99%
“…rhTRAIL is a more favorable therapeutic agent because many cancers have a non-functional TP53 gene that leads to necrosis over ANTICANCER RESEARCH 37: 6593-6599 (2017) 6596 apoptosis, so if chemotherapy and radiation are applied, then negative side effects could be observed in patients. Despite this, there are factors that are implicated in resistance to rhTRAIL that lead to clinical trials being terminated due to the absence of clinical efficacy (25)(26)(27)(28). Our study sought to combat rhTRAIL resistance in TNBC BT-20 and HCC1937 cells through the application of the "mother-nature"-derived silibinin as a sensitizing agent.…”
Section: Discussionmentioning
confidence: 99%